New Technique for Caesarean Section - Vejnović, T. R.; Costa, S. D.; Ignatov, A. (Geburtshilfe und Frauenheilkunde, 2012)
Caesarean section is one of the most common operations worldwide and more than 30 % of procedures in perinatal centres in Germany are caesarean sections. In the last few years the technique used for caesarean sections has been simplified, resulting in a lower postoperative morbidity. But persistent problems associated with all caesarean section techniques include high intraoperative loss of blood, the risk of injury to the child during uterotomy and postoperative wound dehiscence of the uterine scar. We present here a modification of the most common Misgav-Ladach method. The initial skin incision is done along the natural skin folds and is extended intraoperatively depending on the circumference of the babyʼs head. After blunt expansion of the uterine incision using an anatomical forceps, the distal uterine wall is pushed behind the babyʼs head. The babyʼs head is rotated into the occipito-anterior or posterior position and delivery occurs through the application of gentle pressure on the uterine fundus. Closure of the uterotomy is done using 2 continuous sutures, which are then knotted together resulting in a short double-layer closure. The two ends of the skin suture are left open to allow for natural drainage. Our experience at the University Gynaecological Hospitals in Novi Sad and Magdeburg has shown that this modification is associated with shorter operating times, minimal blood loss and shorter in-hospital stay of patients as well as high rates of patient satisfaction.
Keywords: Caesarean section; section modification; Vejnović method